Temas e figuras do mito de Orfeu nas Geórgicas de Virgílio: (Virgílio, Geórgicas, IV, 453-527) - Bertini, Beatriz Scatena [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This research presents the Latin text using the theoretical instrument provided by Linguistics, Poetics and Literary Semiotics, focusing mainly on the aspects of the figurative discourse. Therefore, the perception of the effects of meaning, learned through the reading of the text, was needed in order to discover the resources of selection and combination responsible for these effects. The corpus is an excerpt from Virgil's Georgics (verses number 453 to 527), and, as a result of investigation of this episode that narrates the Myth of Orpheus, a metalinguistic discourse has been produced. This analysis and description of the text concentrated mainly on the first stage of the proceedings of figurativization, when one observes the manifestation of a theme from semiotic figures

Esta pesquisa procura abordar o texto latino a partir do instrumental teórico fornecido pela Linguística, pela Poética e pela Semiótica Literária, focalizando principalmente os aspectos da figuratividade do discurso. Para tanto, buscou-se a percepção dos efeitos de sentido, apreendidos através da leitura do texto, a fim de descobrir os recursos da seleção e combinação responsáveis por esses efeitos. O corpus é um excerto da obra Geórgicas de Virgílio (hex. 453-527), e, como resultado da investigação desse episódio que narra o Mito de Orfeu, foi produzido um discurso metalinguístico no intuito de ressaltar os recursos básicos da figuratividade poética. Essa análise e descrição do texto concentrou-se principalmente na primeira etapa dos procedimentos da figurativização, quando se observa a manifestação de um tema a partir de figuras semióticas
Keywords: Virgilio Geórgicas; Linguística; Literatura latina; Mito; Linguistics